Consumption Trends of Antibiotics in Brazil During the COVID-19 Pandemic - Del Fiol, Fernando de Sá; Bergamaschi, Cristiane de Cássia; De Andrade, Isaltino Pereira; Lopes, Luciane Cruz; Silva, Marcus Tolentino; Barberato-Filho, Silvio (Frontiers in Pharmacology, 2022)
Background: In 2019, a new type of coronavirus emerged and spread to the rest of the world. Numerous drugs were identified as possible treatments. Among the candidates for possible treatment, an association between azithromycin and hydroxychloroquine has been widely propagated and studied in combating new infections. As a result, many clinicians in Brazil have prescribed azithromycin in an attempt to combat or minimize the effects of COVID19. Aim: This study analyzed the sales data of the main antibiotics prescribed in Brazil to verify the change in consumption trends of these drugs during the COVID-19 pandemic. Methods: This is an interrupted time series that analyzed antimicrobial sales data between January 2014 and July 2021, publicly accessible information obtained from the Brazilian government's website. Monthly means of defined daily doses of DDDs (DDDs per 1,000 inhabitants per day) of antibiotics were compared by analysis of variance, followed by the Dunnett Multiple Comparisons Test. Monthly trend changes in antibiotic use were verified using Joinpoint regression. Results: Amoxicillin (31.97%), azithromycin (18.33%), and cefalexin (16.61%) were the most sold antibiotics in Brazil during the evaluation period. Azithromycin consumption rose from 1.40 DDDs in February 2020 to 3.53 DDDs in July 2020. Azithromycin sales showed a significant increase in the pandemic period (Monthly Percent Change [MPC] 5.83%, 95% 1.80; 10.00), whereas there was a fall in amoxicillin sales (MPC -9.00%, 95% CI -14.70; -2.90) and cefalexin (MPC-2.70%, 95% [CI -6.30; -1.10]) in this same period. Conclusion: The COVID-19 pandemic changed the pattern of antibiotic consumption in Brazil, with a decrease in the use of amoxicillin and cefalexin and an increase in the consumption of azithromycin prescribed by physicians, dentists, and veterinarians.